Situation Report: Czechoslovakia, 21 July 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Agriculture and Foodstuffs: How to Attain Self-Sufficiency Foreign Tourism: An Important Factor in Improving the Balance of Payments New Czech Theater Magazine Slovak Minister of Education Replaced